2011
DOI: 10.4196/kjpp.2011.15.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Immunopotentiating Effects of the Glycoprotein Isolated from Dioscorea Batatas

Abstract: W e demonstrate that glycoprotein isolated from Dioscorea batatas (GDB) has immunostimulatory effects including macrophage activation. Analysis of infiltration of inflammatory cells into peritoneal cavity showed GDB treatment significantly increased the recruitment of macrophages, lymphocytes, neutrophils, and monocytes into the peritoneal cavity. Treatment of spleen cells isolated from C57BL/6 mice with GDB significantly increased the proliferation of B cells and T cells induced by LPS and ConA, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…YP‐1, a D. opposita Thunb polysaccharide, could stimulate Con A‐induced T lymphocyte proliferation (Zhao et al, ). D. batatas glycoprotein also exhibits immunopotentiating effects (Huong et al, ). In the present study, the immunoregulation activity and the underlying mechanisms of D. opposita Thunb glycoprotein were explored.…”
Section: Discussionmentioning
confidence: 99%
“…YP‐1, a D. opposita Thunb polysaccharide, could stimulate Con A‐induced T lymphocyte proliferation (Zhao et al, ). D. batatas glycoprotein also exhibits immunopotentiating effects (Huong et al, ). In the present study, the immunoregulation activity and the underlying mechanisms of D. opposita Thunb glycoprotein were explored.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, macrophages produce a number of cytotoxic molecules, such as, NO [9], which is also cytotoxic to certain tumor cells [28]. In a previous study, we found that GDB can exert significant immunomodulatory effects on specific immune responses mediated by macrophages, lymphocytes, and NK cells in vitro and in vivo [7]. GDB treatment of C57BL/6 mice caused a significant increase in the numbers of lymphocytes and macrophages in the peritoneal cavity, and both of these cell types play important roles in the first line of immunological defense against tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two proteins identified in D. alata tubers, dioscorins and phytoglycoproteins [33,34] are known to activate MAP kinases (ERK, p38, and JNK) and NF-κB via the TLR-4 signal transduction pathway and increases the expressions of pro-inflammatory cytokines, such as, TNF-α, IL-1β, and IL-6, in several cells including RAW 264.7 macrophages, murine monocytes, and human monocytes [4,35]. We previously isolated glycoprotein from Dioscorea batatas , and characterized and demonstrated its immunostimulatory activity [7]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations